EFEITO DA DENSIDADE DE CRIAÇÃO NO DESEMPENHO PRODUTIVO DE FRANGOS DE CORTE ROSS 308 NA FASE INICIAL (1-21 DIAS) - CASSUCI, Leticia Gabriela Talhaferro; DE SOUZA Andreia Fróes Galuci Oliveira; SILVA, Higor Jonathan de Oliveira; DA COSTA, Gabriela da Silva; SILVA, Maria Vitória; DOMINGUES, Elyan Carlos Da Silva (ANAIS DO ENIC, 2022)
-